2021
DOI: 10.3390/nu13062027
|View full text |Cite
|
Sign up to set email alerts
|

Intersection between Obesity, Dietary Selenium, and Statin Therapy in Brazil

Abstract: Obesity is among the most alarming health concerns, impacting public health and causing a socioeconomic challenge, especially in developing countries like Brazil, where approximately one quart of the population presents obesity. As an established risk factor for numerous comorbidities with a multifactorial etiology, obesity is a consequence of energy-dense overfeeding, however with significant undernourishment, leading to excessive adipose tissue accumulation and dysfunction, dyslipidemia, and micronutrient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Statins inhibit cholesterol synthesis via the mevalonate pathway, an important pathway for selenoprotein synthesis. Therefore, subjects who use statins are at an increased risk of developing Se deficiency and oxidative stress [ 56 , 57 ]. BN is a source of Se and may help maintain the nutritional status and oxidative balance of Se in patients using statins.…”
Section: Resultsmentioning
confidence: 99%
“…Statins inhibit cholesterol synthesis via the mevalonate pathway, an important pathway for selenoprotein synthesis. Therefore, subjects who use statins are at an increased risk of developing Se deficiency and oxidative stress [ 56 , 57 ]. BN is a source of Se and may help maintain the nutritional status and oxidative balance of Se in patients using statins.…”
Section: Resultsmentioning
confidence: 99%
“…Dyslipidemia is a powerful and prevalent risk factor for the development and progression of atherosclerosis and CVD ( 2 , 20 ). Typical dyslipidemia consists of increased triglycerides (TG) and free fatty acids, decreased high-density lipoprotein cholesterol (HDL), and normal or slightly increased low-density lipoprotein cholesterol (LDL) ( 6 ). Recently, Sun et al ( 11 ), studying traits for which the Native Hawaiians exhibit excess risk, observed that 2,239 individuals (56.8%) presented hyperlipidemia (or dyslipidemia), in which 657 individuals were undiagnosed.…”
Section: Facets Of Cardiometabolic Disorders In Nhopimentioning
confidence: 99%
“…Thus, studies and current guidelines have focused on aggressive LDL-C lowering with a statin in both primary and secondary intervention settings ( 2 , 4 , 5 ). Nevertheless, significant side effects, such as muscle disorders, have been associated with statin use ( 6 ). The occurrence of statin side effects varies among different ethnic groups and is associated with individual intrinsic factors or external aspects ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is among the most alarming global public health problems [1]. It is associated with premature mortality and increases the burden of non-communicable diseases [2]. Importantly, in men, obesity is also linked to deregulation of reproductive physiology [3].…”
Section: Introductionmentioning
confidence: 99%